Axon reflex-related hyperemia induced by short local heating is reproducible - Huang, Chung-Shin; Wang, Shwu-Fen; Tsai, Yuan-Feen (Microvascular research, 2012)
The axon reflex (AR) flare is induced by antidromic activation of afferent C-fibers during nociceptive stimulation. This response has been suggested to be modulated by sympathetic activity and basal level of nitric oxide. In previously used protocols of local thermal hyperemia (LTH), AR flare has been used in combination with maximal vasodilatation to study the integrated endothelial function. The aim of this study was to investigate the intra-session reproducibility of short heating-induced AR flare, the specific neural-mediated portion of LTH, and to compare the reproducibility between different forms of data expression. Short-heating LTH was assessed using single-point laser Doppler flowmetry (LDF) on bilateral volar surface of the forearm in 10 men and 10 women. The blood flux measurement included a non-heating process for 5min, followed by a quick heating process from 33°C to 42°C for 5min. The test was repeated 45min later at the same recording sites with fixed holders. Baseline and heating blood flux were recorded and expressed as different forms of data. Reproducibility was assessed using coefficient of variation (CV) and intra-class correlation coefficient (ICC) statistics. The reproducibility of peak cutaneous vascular conductance (CVC) (CV=16.02–17.31%, ICC=0.77–0.78), peak CVC change (CV=14.30–18.12%, ICC=0.80–0.86), and the 4min area-under-the-curve (CV=18.37–18.70%, ICC=0.60–0.78) was acceptable. The time to peak flux of each recording site ranged from 90 to 209s and all the peak fluxes have been achieved before 4min of heating. Single-point LDF is a reproducible technique of assessing AR flare on volar surface of the forearm when the heating period is reduced to 5min and the recording sites are fixed. Using this new protocol, short-heating LTH has a potential to be used to evaluate the effects of acute physical or chemical interventions between two short-heating LTH tests to further explore the pathophysiological meaning of heating-induced AR flare. ► The heating period of local thermal hyperemia was reduced from 30 to 50min to 5min. ► Short-heating protocol tested hyperemia specifically mediated by the axon reflex. ► We fixed the recording site for local heating and blood flow measurement. ► The heterogeneities of capillary density and sensory innervation were controlled. ► Short-heating protocol was reproducible without using data from longer heating.